2014
DOI: 10.1089/neu.2013.3042
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference Is the Best Index for Obesity-Related Cardiovascular Disease Risk in Individuals with Spinal Cord Injury

Abstract: Obesity is an important identifier of cardiovascular disease (CVD) risk, but is challenging to determine accurately in individuals with spinal cord injury (SCI). Body mass index (BMI) is used worldwide as a simple indicator of obesity, but is difficult to measure in individuals with SCI. Furthermore, standard BMI cutoffs underestimate obesity in this population. Therefore, we aimed to identify the best marker of obesity in individuals with SCI, considering both practicality, and ability to detect adiposity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 52 publications
8
66
0
2
Order By: Relevance
“…15 We recently showed that WC was the best measure of obesityrelated CVD risk after SCI. 16 In this study, BMI was strongly correlated with adiposity, but not with CVD risk. However, the impact of different scaling factors for height correction in individuals with SCI is unknown, and may improve the relationships between these measures, as has been shown in the able-bodied.…”
Section: Introductionmentioning
confidence: 45%
See 4 more Smart Citations
“…15 We recently showed that WC was the best measure of obesityrelated CVD risk after SCI. 16 In this study, BMI was strongly correlated with adiposity, but not with CVD risk. However, the impact of different scaling factors for height correction in individuals with SCI is unknown, and may improve the relationships between these measures, as has been shown in the able-bodied.…”
Section: Introductionmentioning
confidence: 45%
“…16 The study received ethical approval from the Research Ethics Committee at Simon Fraser University and the Vancouver Coastal Health Research Institute. Measurements were taken on individuals with chronic SCI (41 year), who gave written informed consent, had no known pre-existing (prior to injury) CVD and were not taking any cardiovascular-related medications.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations